Paeoniflorin, ferulic acid, and atractylenolide III improved LPS-induced neuroinflammation of BV2 microglia cells by enhancing autophagy - Xiaolan Zhou; Xingru Chen; Xiaoqing Cheng; Liting Lin; Shijian Quan; Shijun Li; Ruoting Zhan; Qingguang Wu; Sijun Liu (Elsevier, 2023)
Microglia hyperactivation is an important cause of neuroinflammation in Alzheimer's disease (AD). Paeoniflorin (PF), ferulic acid (FA), and atractylenolide III (ATL) are potent in anti-inflammation and neuroprotection. Multiple components can act on different targets simultaneously to exert synergistic therapeutic effects and exploring the synergistic potential between compounds is an important area of research. We investigated the effects of PF, FA, and ATL, alone or in combination, on LPS-induced neuroinflammation and autophagy in BV2 microglia cells. We found that PF, FA, and ATL, alone or in combination, significantly reduced the production of inflammatory factors such as IL-6, IL-1β, and TNF-α, especially in the PF + FA + ATL group, which performed the best. In addition, the combination of PF, FA, and ATL significantly increased the expression of autophagy-related proteins p-AMPK, p-ULK1, Beclin1, LC3, and TFEB and decreased the expression of p62. Moreover, the restoration of autophagic flux by the combination of PF, FA, and ATL was abrogated by the addition of the autophagy inhibitor Wortmannin. In conclusion, PF, FA, and ATL have a synergistic effect in reducing LPS-induced inflammatory factor release from BV2 microglia cells, and its protective effect may be through activation of the AMPK/ULK1/TFEB autophagic signaling pathway.